(untitled) (GYMNASIUM, 2009)
The development of psycho-motrical abilities in 11 – 14 year old children is a good motivation for monitoring some of the specific aspects during this age period by analyzing the weight of the main training means over the annual cycle. The research was achieved through an integrative approach of the training by correlating the subjects’ growth and development characteristics with methodical training requirements specific to the age group. The progress obtained by the subjects during the second test series after running through the adopted training pattern confirms the correctness of the adopted methodical orientation. Progress of physical training level and physical development corresponds with the stage of growth and development of the subjects. Significant progress was obtained in both mo